Decision Support System for facility location problems in fleet management - Martins, João Miguel Faria (2021)
Businesses that are growing by providing more services, reaching more customers or improving their business strategy, might need to create or relocate a facility location to expand the geographical coverage and improve their services. This decision is complex, and it is crucial to analyse their client locations, journeys and be aware of the factors that may affect their geographical decision. These organisations must weigh all these factors, such as security levels, taxes or costs due to the importance and impact that they can have in the short and long term business strategy. Therefore, the decision-maker needs to ensure that the location is the most profitable site according to the business scope and future perspectives. To help the businesses on this complex decision, this dissertation details the development of a Decision Support System (DSS) capable of providing facility location suggestions based on the existing journeys and the factors that the decision-maker considers more relevant to the company. The developed DSS has three main components: (1) Decision Support System; (2) Geospatial Analysis System; and (3) Facility Location Factors System. The Decision Support System is responsible for producing ordered facility location suggestions by performing the multicriteria decision analysis (MCDA) that implements the TOPSIS algorithm. The Geospatial Analysis System, through the use of the DBSCAN algorithm, is responsible for retrieving the alternatives by identifying the geospatial clusters based on the existing journeys. Lastly, the Facility Location Factors System is responsible for retrieving the criterion by gathering the data from external sources according to the chosen factors. The evaluation analysis shows that the perspective of the users about the assistance of the system by helping them choose appropriate facility location is favourable. This analysis showed that the users agree about the accuracy and the value of the facility location suggestions. The output helps the business managers to make better decisions by returning facility locations that have potential to maximise the company’s profit by reducing transportation and fuel costs and maximise the number of covered customers by expanding their territorial coverage. This project handles data provided by Fonix Telematics from their United Kingdom clients that have relevance to the study, such as a high number of assets, journeys and geographical coverage.